2013
DOI: 10.1080/09540105.2013.768963
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the association ofBF1/BF2 gene expression patterns with traits of genetic resistance to Marek's disease in chickens

Abstract: 2014)Studies on the association of BF1/BF2 gene expression patterns with traits of genetic resistance to Marek's disease in chickens, Food and Agricultural Immunology, 25:2, 220-228,The aim was try to clarify the association of BF1 and BF2 gene expression patterns with the traits of genetic resistance to Marek's disease (MD) in chickens. An MD-resistant line and a common line of Xiayan chickens were used in the experiment. The productions of mRNA of BF1 and BF2 and Marek's disease virus (MDV) gene, meq, were q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The Xiayan is a well‐known and the largest local line of the meat‐type chicken in China. During about 5 years of research, we have arrived at almost the same conclusion that we present in this study . Also, in narrowing down the BF gene further to it's alternative exon 7 splice variant and especially in developing a snPCR assay that amplifies the alternative exon 7 splice variant of the BF gene , we have increased the chance for the rapid detection of resistant/susceptible BF haplotypes to MD .…”
Section: Discussionsupporting
confidence: 71%
“…The Xiayan is a well‐known and the largest local line of the meat‐type chicken in China. During about 5 years of research, we have arrived at almost the same conclusion that we present in this study . Also, in narrowing down the BF gene further to it's alternative exon 7 splice variant and especially in developing a snPCR assay that amplifies the alternative exon 7 splice variant of the BF gene , we have increased the chance for the rapid detection of resistant/susceptible BF haplotypes to MD .…”
Section: Discussionsupporting
confidence: 71%
“…The 20 N-terminal amino acid sequences of the 37 kDa OMP have a high homology to glyceraldehyde-3-phosphate dehydrogenase (GAPDH), which catalyzes glycolysis in eukaryotes. GAPDH is also found on the bacterial cell surface and is used as a house keeping gene and protein in quantitative polymerase chain reaction (PCR) and western blot analysis respectively (Jin, Wei, Niu, Li, & Yang, 2014;Ueno, Nishiguchi, Takeshita, Yamaguchi, & Oda, 2017;Wu et al, 2012;Yu et al, 2011;Zainuddin, Chua, Rahim, & Makpol, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…BF1 was poorly transcribed and BF2 well transcribed at a ratio varying from 1.5 to 33, supporting the 'minimal essential MHC' hypothesis that a single dominant class I molecule (BF2) determines MHC haplotype-associated differences in disease resistance. Previously, Wei [1] found that the expression modes of BF1 and BF2 genes might be related to traits of genetic resistance to MD in the chicken. However, variation in amino acid sequences between the full-length BF1 and BF2 mRNA transcripts has not been compared.…”
mentioning
confidence: 99%